High-quality graphene on single crystal Ir(1 1 1) films on Si(1 1 1) wafers: Synthesis and multi-spectroscopic characterization. (January 2015) - Struzzi, C.; Verbitskiy, N.I.; Fedorov, A.V.; Nefedov, A.; Frank, O.; Kalbac, M.; Di Santo, G.; Panighel, M.; Goldoni, A.; Gärtner, J.; Weber, W.; Weinl, M.; et al.
Abstract: The characterization of graphene by electron and optical spectroscopy is well established and has led to numerous breakthroughs in material science. Yet, it is interesting to note that these characterization methods are almost never carried out on the same sample, i.e., electron spectroscopy uses epitaxial graphene while optical spectroscopy relies on cleaved graphene flakes. In order to bring coherence and convergence to this branch, a universal and easy-to-prepare substrate is needed. Here we suggest that chemical vapour deposition (CVD) grown graphene on thin monocrystalline Ir(1 1 1) films, which are grown heteroepitaxially on Si(1 1 1) wafers with an yttria stabilized zirconia (YSZ) buffer layer, perfectly meets these needs. We investigate graphene prepared in this way by low-energy electron diffraction (LEED), X-ray photoelectron spectroscopy (XPS), near edge X-ray absorption fine structure (NEXAFS) spectroscopy, angle-resolved photoemission spectroscopy (ARPES), resonance Raman spectroscopy, and scanning tunnelling microscopy (STM). Our results highlight the excellent crystalline quality of graphene, comparable to graphene prepared on Ir(1 1 1) bulk single crystals. This synthesis route allows for large-area, inexpensive growth on standardized disposable substrates, suitable for both optical and electron spectroscopic characterization, which meets the needs of many researchers in the field.